CRISPR/Cas9‐mediated targeting of the Rosa26 locus produces Cre reporter rat strains for monitoring Cre–loxP‐mediated lineage tracing. (19th September 2017) - Ma, Yuanwu; Yu, Lei; Pan, Shuo; Gao, Shan; Chen, Wei; Zhang, Xu; Dong, Wei; Li, Jing; Zhou, Rui; Huang, Lan; Han, Yunlin; Bai, Lin; et al.
Abstract : The rat is an important laboratory animal for physiological, toxicological and pharmacological studies. Clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR‐associated 9 (Cas9) is a simple and efficient tool to generate precise genetic modifications in rats, which will promote the accumulation of genetic resources and enable more precise studies of gene function. To monitor Cre– loxP ‐mediated excision in vivo, we generated a Cre reporter rat strain ( Rosa26‐imCherry ) by knockin of a Cre reporter cassette at the Rosa26 locus using CRISPR/Cas9. Rosa26‐imCherry rats exhibited inducible expression of the mCherry cassette ( imCherry ) using the Cre –loxP system, whereas normal rats exhibited ubiquitous expression of eGFP but not mCherry in the whole body. Injection of adeno‐associated virus serotype 9– Cre into the hippocampus and skeletal muscle resulted in mCherry expression in virus‐infected cells. Cre –loxP ‐mediated mCherry expression was then evaluated by crossing Rosa26‐imCherry rats with transgenic rats ubiquitously expressing CAG ‐ Cre, heart‐specific α‐ MHC‐Cre transgenic rats and liver‐specific Alb‐Cre knockin rats. Finally, using the established system the expression pattern of Cre driven by two endogenous gene promoters ( Wfs1‐Cre knockin rat, FabP2‐Cre knockin rat) was traced. In summary, we demonstrated excision of the loxP ‐flanked allele in Rosa26‐imCherry rats via activation of mCherry expression in the presence of Cre recombinase. This newly established Rosa26‐imCherry rat strain represents a useful tool to facilitate Cre ‐expression pattern determination and tracing experiments. Abstract : To monitor Cre– loxP ‐mediated excision in vivo, a Cre reporter rat strain ( Rosa26‐imCherry ) was generated using CRISPR/Cas9. Cre– loxP ‐mediated mCherry expression was evaluated by crossing Rosa26‐imCherry rats with transgenic rats ubiquitously expressing CAG ‐ Cre . Ubiquitous mCherry expression in double‐positive offspring was observed. This newly established rat strain represents a useful tool to facilitate Cre ‐expression pattern determination and tracing experiments.